(untitled) (Medico Legal Update, 2020)
A burn is an injury which is caused by application of heat or chemical substances to the external or internal surfaces of the body, which causes destruction of the tissues. The magnitude of deaths due to burns is so large in our country that India is the only country in the world where fire is classified among the fifteen leading causes of death. The purpose of this study is to analyze profile of burn deaths in the Pune region of Maharashtra. In the present study among the 1710 burn deaths, females (70%) are more commonly affected than males (30%). Young adults (21–40 yrs) are commonly involved in fatal burns as this is most active group of population. In present study majority cases happened in summer season and were accidental in nature while suicidal deaths were present in significant number. Flame burns comprised of 80% of the cases followed by scald 13%. In 78% of cases more than 50 % of total body surface area was involved while complications like Septicemia (66%) was commonest cause of death.